Oxidative Stress Regulated Iron Regulatory Protein IRP2 Through FBXL5-Mediated Ubiquitination-Proteasome Way in SH-SY5Y Cells - Jiao, Qian; Du, Xixun; Wei, Jie; Li, Yong; Jiang, Hong (Frontiers in Neuroscience, 2019)
Iron regulatory protein 2 (IRP2) plays a key role in the cellular iron homeostasis and could be regulated by a variety of factors, such as oxidative stress, hypoxia and iron, etc. IRP2 depletion results in neurodegenerative movement disorder with the loss of neurons and accumulations of iron. Since oxidative stress extensively exists in several neurodegenerative diseases where iron accumulation also exists, it is important to clarify the mechanisms underlying the effects of oxidative stress on IRP2 expression and its consequence. 200 and 300 μM H2O2 could result in the reduced cell viability in SH-SY5Y cells. The intracellular levels of reactive oxygen species (ROS) were increased by 52.2 and 87.3% with 200 and 300 μM H2O2 treatments, respectively. The decreased levels of mitochondrial transmembrane potential (ΔΨm) were only observed in 300 μM H2O2-treated group. The protein levels of IRP2, but not for its mRNA levels, were observed decreased in both groups, which resulted in the lower TfR1 expression and decreased iron uptake in these cells. Pretreatment with MG132, the decreased IRP2 levels caused by H2O2 treatment could be antagonized. The protein levels of F box and leucine-rich repeat protein 5 (FBXL5), the only E3 ligase of IRP2, were observed decreased accordingly. When knockdown the intracellular FBXL5 levels by si-FBXL5, the protein levels of IRP2 were found increased with H2O2 treatment. Our results suggest that FBXL5 is involved in the degradation of IRP2 under oxidative stress in dopaminergic-like neuroblastoma cells, which implies that its role in the neuronal regulation of IRP2 in neurodegenerative diseases.